Effect of Pilates Training and Resveratrol on Serum Levels of Endoplasmic Reticulum Stress Indicators in Middle-Aged Obese Women in Tehran - Nina Alipour Ghazichaki; Ahmad Abdi; Alireza Barari (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Perturbation of the endoplasmic reticulum (ER) homeostasis is known as one of the prominent features of obesity. Combining a healthy diet and exercise can improve health and performance. The aim of this study was to investigate the effect of Pilates training (PT) and resveratrol (RSV) on endoplasmic reticulum stress indicators in middle-aged obese women. Materials and methods: In this clinical trial, 40 obese adult women with the mean age of 42.74±5.70 years and body mass index of 31.76±1.37 kg/m2 in Tehran were randomly allocated into four groups; Placebo (C), Pilates Training (PT), Resveratrol (RSV), and Pilates Training-Resveratrol (PTRSV). The PT groups did the training program with 14-16 RPE for 8 weeks, 3 times/week. The RSV and PTRSV groups were provided with 500 mg RSV tablets every morning. Data were analyzed using independent t-test and ANCOVA. Results: According to findings, PT and RSV decreased Glucose-regulating protein 78 (GRP78) (P=0.001 and P=0.007, respectively) and Tribbles homolog 3 (TRB3) (P=0.0001 and P=0.0001, respectively). Simultaneous intervention of PT and RSV also reduced GRP78 and TRB3 more than other groups (P<0.05). Conclusion: PT and RSV supplementation could improve the endoplasmic reticulum stress in middle-aged obese women by altering the levels of GRP78 and TRB3. However, the simultaneous effect of PT and RSV was found to be better on these indices.